Seroprevalence and risk factors associated to infection by Trypanosoma cruzi and Toxoplasma gondii in the Saimadoyi community, Sierra de Perija, Zulia state - Milagros Paz O; Odelis Díaz-Suárez; Ricardo Atencio; Zulbey Rivero- Rodríguez; Raikelin Terán M; Angela Bracho; M. Soler; M. Suárez (Kasmera, 2017)
Chagas disease and toxoplasmosis are health problems characteristic of rural areas. The aim of this research was to determine the seroprevalence of Trypanosoma cruzi y Toxoplasma gondii. in community Saimadoyi. 166 serum samples from individuals of both sexes (100 female 66 male and) aged 1-83 years were studied. The determination of antibodies was performed by ELISA using a commercial kit. Trypanosoma cruzi seroprevalence was 51% (87/166), while for Toxoplasma gondii was 57% (95/166). Most positive cases were found in people under 20 years old, however no significant differences with regard to gender or age group for both parasites were found. Epidemiological data showed statistically significant risk factors (p <0.05) for T. cruzi infection were the type of housing, contact with dogs or chipos and soil contamination with feces; while for T. gondii infection, contact with cats and poor hygiene were the significant risks. The high number of seropositives cases in women of reproductive age suggests vertical transmission of both parasites.